Estimating Equilibrium Exchange Rates for Armenia and Georgia - Ding, Shuang; Al Shehabi, Omar. (Washington, D.C. : International Monetary Fund, 2008)
The significant real exchange rate appreciation in Armenia and Georgia since 2003, coupled with persistent current account deficits, raises the question of whether real exchange rates have become overvalued. This paper seeks to identify possible exchange rate misalignment by applying the behavioral equilibrium exchange rate approach, complemented by an analysis of the traditional competitiveness indicators. The results indicate an undervaluation of the Armenian dram and no significant misalignment of the Georgian lari in 2006.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet